PROBLEMS IN LENDING INDIVIDUALS IN COMMERCIAL BANKS AND WAYS TO ELIMINATE THEM - Zokir Mamadiyarov; Sarvar Askarov (Journal of Artificial Intelligence and Digital Economy, 2024)
In this article, banks are in the process of digital transformation Problems and current situation in improving retail banking services are analyzed. In particular, in the transformation of the banking system of Uzbekistan, the revision of the bank structure and the optimization of the bank's service processes, the one-step lending system through underwriters and the management of personal funds for users are the most important. comments on the applications. The results of this study are important in studying the factors influencing the development of retail banking services and eliminating problematic situations